Rediseño del sistema de control de velocidad de un motor de corriente directa de 600HP con variador de velocidad SINAMICS (2022)
This project shows the step by step to upgrade a power electronics system with basic 2- quadrant technology to a more modern one with 4-quadrant technology, from information gathering, selection of control strategy, redesign and implementation. taking into account that this change also includes improvement in electrical control and industrial communication protocols allowing better control of the equipment, since there will be more signals available for it, better energy efficiency, safety and integrity through PLC protections and fine parameter setting in the Drive that is not available in the current power system